Platycodon grandiflorum, as a medicinal and food homologous plant: a comprehensive review of anti-tumor components, mechanisms, modern applications, and preventive healthcare - Liu, Wenjing; Jia, Shumin; Ma, Xiaoyan; Lu, Doudou; Du, Yuhua; Zhou, Ziying; Yuan, Ling; Yu, Rong; Nan, Yi (Frontiers in Nutrition, 2025)
Platycodon grandiflorum (Jacq.) A. D C. (P. grandiflorum), as a medicinal and edible plant, is widely distributed in China. In terms of Chinese medical theories, Traditional Chinese Medicine (TCM) believes that the root of P. grandiflorum has the functions of relieving sore throat, eliminating phlegm, and draining pus, and is widely used in lung diseases and respiratory system disorders. Modern pharmacological studies have shown that Platycodon grandiflorum saponin, flavonoids, polysaccharides, and phenolic acids are the main active components of P. grandiflorum, which have significant antitussive, expectorant, anti-tumor, anti-oxidation and hypoglycemic effects. In recent years, an increasing number of research evidence has demonstrated the anticancer potential of P. grandiflorum. In this study, we firstly identified the anti-tumor active components of P. grandiflorum (platycodin D, P. grandiflorum polysaccharides, lobetyolin, luteolin, and apigenin) as well as their mechanism of action in inhibiting cancer cell proliferation (inducing apoptosis, blocking the cell cycle and inhibiting tumor metastasis). Additionally, we investigated the detoxification and synergy-enhancing effects of these active components when combined with chemotherapeutic drugs, as well as the improvement of their drug delivery and the bioavailability through nano-delivery systems, which hold great anticancer potential for clinical application. However, research on the anti-tumor effects of P. grandiflorum extract and its active components still lacks large-scale clinical trials. Finally, we further summarized the applications of P. grandiflorum in preventive healthcare, emphasizing its dual value in the pharmaceutical and food industries. This summary provides a scientific basis for further research on its anti-tumor properties and highlights its potential development in modern preventive healthcare.